An efficient method for the preparation of magnetic Co3O4 nanoparticles and the study of their catalytic application - Ardeshirfard, Hakimeh; Elhamifar, Dawood (Frontiers in Catalysis, 2023)
In this study, magnetic cobalt oxide nanoparticles (Co3O4) have been synthesized through a new and green method by using cobalt chloride hexahydrate (CoCl2.6H2O), pluronic P123 as a stabilizer and sodium borohydride (NaBH4). The CO3O4 nanoparticles were characterized by using diffuse reflectance infrared Fourier transform spectroscopy (DRIFTs), powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray (EDX) spectroscopy, scanning electron microscopy (SEM) and vibration sample magnetometer (VSM). The magnetic Co3O4 NPs were used as a catalyst with high activity and stability in the synthesis of tetrahydrobenzo[b]pyran derivatives. This reaction was carried out in the water as an environmentally friendly solvent by using a low loading of Co3O4 NPs at room temperature. Various derivatives of aldehydes were used as substrates to give corresponding tetrahydrobenzo[b]pyrans in a high yield at short times. In addition, the catalyst was recovered and re-used several with no a notable decrease in its activity.